2020
DOI: 10.3892/ol.2020.12326
|View full text |Cite
|
Sign up to set email alerts
|

β‑hydroxybutyrate does not alter the effects of glucose deprivation on breast cancer cells

Abstract: Ketogenic diets have the potential to lower glucose availability to cancer cells. However, the effect that the resulting increase in ketone bodies has on cancer cells is not fully understood. The present study explored the effect of β-hydroxybutyrate (BHB) on glucose-deprived MCF-7 and T47D breast cancer cells. Cell proliferation was decreased in response to lower glucose conditions, which could not be rescued consistently by 10 or 25 mM BHB supplementation. In addition, gene expression levels were altered whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 63 publications
2
3
0
Order By: Relevance
“…Chen et al [47] reported that short term glucose deprivation (24 h) in various breast cancer cell lines induced cell death, which was higher in MDA-MB-231 than MCF-7 cells, in part through enhanced AMPK phosphorylation. This was also observed in another report using MCF-7 and T47D cells [48]. We did not see much difference in cell proliferation at 24 h; it was evident at day 4 of glucose starvation in both the cancer lines as well as the normal cells.…”
Section: Discussionsupporting
confidence: 89%
“…Chen et al [47] reported that short term glucose deprivation (24 h) in various breast cancer cell lines induced cell death, which was higher in MDA-MB-231 than MCF-7 cells, in part through enhanced AMPK phosphorylation. This was also observed in another report using MCF-7 and T47D cells [48]. We did not see much difference in cell proliferation at 24 h; it was evident at day 4 of glucose starvation in both the cancer lines as well as the normal cells.…”
Section: Discussionsupporting
confidence: 89%
“…1 G). This is notable as previous literature reports have not shown a significant effect of βHb on breast cancer cell proliferation [ 38 ]. While normal cells display density-dependent inhibition of proliferation, entering quiescence at maximal concentration, cancer cells show no density-dependent inhibition and continue growing even at high cell densities [ 39 ].…”
Section: Discussionsupporting
confidence: 51%
“…In a breast cancer study (Dai et al, 2017), researchers cultured MCF-7 and T47D breast cancer cells with different glucose concentrations and found that low glucose concentration significantly inhibited the proliferation of breast cancer cells. Moreover, signal pathway enrichment analysis showed that the Hippo-Yap cell signaling pathway in MCF-7 breast cancer cells was downregulated when the glucose concentration in the culture environment was reduced, whereas the expression of NRF2 pathway-related genes in T47D breast cancer cells was significantly increased (Maldonado et al, 2021). In a recent lung cancer study, researchers found that glucose metabolism disorders may be closely associated with the carcinogenesis of lung cancer, which suggests that glucose metabolism may be a potential therapeutic target for lung cancer (Ding et al, 2019).…”
Section: Glucose Metabolism Reprogramming In Cancer Progressionmentioning
confidence: 99%